Analysis of Community Understanding in Dua Boccoe District, Bone Regency towards the General Election Process - Sarifuddin, Sarifuddin; Hasanuddin, Hasanuddin; Rasyid, Andi Tabrani (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2025)
This research aims to find out how the people in Dua Boccoe District, Bone Regency understand the General Election process. The type of research used is a qualitative research method. The data processed is the result of interviews with the people of Dua Boccoe District as many as 8 (eight) people. The data collection methods used in this research are observation, interviews and document study, where the author directly sees the situation in the field. The research results obtained by the author are that the people of Dua Boccoe District have a clear understanding of the general election process, where everyone can read and understand all realities. Understanding the existing election process is part of the community's way of making choices in every election contest. Through the election process, it is hoped that quality leaders will be born who will of course be able to make this nation much better.